Analysis of temporal variability (2004-2023) in corn production in the municipality of Cuité, Paraíba - Alves, Emily Mirlene da Costa; Carmo, Ellen Vitória Barbosa do; Medeiros, Isabel Lopes de; Silva, Lucas Santos da; Barbosa, Artur Mineu da Silva; Bispo, Pauline Emanuele Mendes; Barbosa, Vitor Mineu da Silva; Santos, José Matheus Gonzaga; Santos Marília Almeida dos; Martins, Leonardo Marques; Gouveia, Fernanda do Nascimento; Nascimento, Júlio César Soares do; et al. (Brazilian Journal of Production Engineering, 2025)
Maize plays a vital role in agriculture due to its productive potential and economic value. Adapted to various environments, it significantly contributes to job and income generation, boosting local and regional production chains. For efficient and profitable cultivation, the adoption of proper management practices is essential. With modern technologies and sustainable strategies, maize productivity can reach higher levels. This study aimed to analyze the maize production dynamics in Cuité, Paraíba, from 2004 to 2023, to understand the factors affecting this production chain and provide support for public policies to strengthen the activity in the region. During the analyzed period, maize production in Cuité showed unsatisfactory results in key observed variables. This low performance is mainly due to the use of traditional agricultural techniques, leading to soil degradation and intensive chemical input use, which negatively impacted sustainability. Additionally, inadequate infrastructure and the lack of efficient public policies hindered farmers’ access to more competitive markets, limiting expansion opportunities. Given this context, it is crucial to adopt sustainable agricultural practices alongside policies that promote technical training for farmers and improve local infrastructure. This approach will help foster a more solid, economically viable, and environmentally sustainable maize production in Cuité.